2019
DOI: 10.1016/j.parepi.2019.e00099
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of cutaneous leishmaniasis in Golestan Province, Iran: A cross-sectional study of 8-years

Abstract: BackgroundLeishmaniasis occurs with an incidence of 0.5–1.5 million new cases annually, and is also endemic in 88 countries across the world.AimPresently, we aimed to investigate the status of Cutaneous Leishmaniasis (CL) in Golestan Province in North of Iran.MethodsA retrospective survey was conducted on existed data of 6873 patients with CL who attended to Health Centers in Golestan Province during 2010 to 2017 years. Data were collected using patient sheets and online registry form of CL. Descriptive statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 14 publications
7
11
0
Order By: Relevance
“…In the present study, most of the patients were male, which is in accord with the results of other studies in Golestan ( Jorjani et al, 2019 ), Mazandaran ( Ghavibazou et al, 2019 ), Northkhorasan ( Alavinia et al, 2009 ) and Qom ( Rostami et al, 2013 ) provinces, and also the study carried out over four decades in Iran ( Piroozi et al, 2019 ). The higher leishmaniasis cases in men seems to be due to more outdoor activity and less coverage compared with women wearing Hijab in Muslim countries, leading to being bitten more by sand flies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, most of the patients were male, which is in accord with the results of other studies in Golestan ( Jorjani et al, 2019 ), Mazandaran ( Ghavibazou et al, 2019 ), Northkhorasan ( Alavinia et al, 2009 ) and Qom ( Rostami et al, 2013 ) provinces, and also the study carried out over four decades in Iran ( Piroozi et al, 2019 ). The higher leishmaniasis cases in men seems to be due to more outdoor activity and less coverage compared with women wearing Hijab in Muslim countries, leading to being bitten more by sand flies.…”
Section: Discussionsupporting
confidence: 92%
“…They are the active age group who might be exposed to sand fly bites due to the existing sand fly breeding places and reservoir host colony near human dwellings in the study area. This finding is in accordance with studies conducted in Golestan ( Jorjani et al, 2019 ) and Kerman ( Khosravi et al, 2017 ) provinces, in northern and southeastern Iran, respectively. However, contradict with studies conducted in the areas with low endemicity of CL such as Mazandaran ( Ghavibazou et al, 2019 ), in northern and Kashan ( Moein et al, 2018 ), in central Iran, which reported the highest incidence in the age group of 20–29 years.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, there was an increase in the incidence rates in the second period. Such casuistry was observed in Brazil from 1985 onwards, where an increasing number of cases presented transmission peaks every 5 years 3 , corresponding to the increasing incidence observed in the provinces of Iran 29,31,32 and Ethiopia 30 . Moreover, the increased incidence may be related to the anthropic actions due to socioeconomic pressure, especially the disordered urbanization that contributes to the domination of the sandfly responsible for transmission of the disease [10][11][12][13] .…”
Section: Discussionmentioning
confidence: 73%
“…Located in the north of Iran, Golestan province is characterized by its geographical, climatic, and ecological diversity as well as the movement of population within and outside of it, and is witness to common and endemic contagious diseases such as animal bites, CL, and Brucellosis. CL and some cases of visceral Leishmaniasis have long existed in north and north-eastern areas of the province around Maraveh Tappeh and Gonbad-e Kavous counties as a prevalent and endemic disease [10].…”
Section: Introductionmentioning
confidence: 99%